2017
DOI: 10.1016/j.healun.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte aging as a mechanism of anemia and a biomarker of device thrombosis in continuous-flow left ventricular assist devices

Abstract: Erythrocyte lifespan is substantially reduced in subjects with a CF-LVAD, which was more pronounced in the presence of device thrombosis. The etiology of anemia in CF-LVAD was primarily due to accelerated erythrocyte aging. Further studies are needed to determine whether erythrocyte lifespan could provide a practical means of detecting subtle pre-clinical thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Increasing and decreasing hematocrit levels in the blood can have an impact on blood viscosity. The greater the percentage of hematocrit levels, the blood viscosity will increase (Taimeh et al, 2017) ; (Hariyadi, 2015) This research is in line with one in Surakarta, namely an increase in hemoglobin levels in pregnant women after giving 350 gram long bean leaves for 30 days (Prastika et al, 2016). Other research have shown increased levels of hematocrit in pregnant women after consuming green bean juice (Anastasia S et al, 2017).…”
Section: Resultssupporting
confidence: 76%
“…Increasing and decreasing hematocrit levels in the blood can have an impact on blood viscosity. The greater the percentage of hematocrit levels, the blood viscosity will increase (Taimeh et al, 2017) ; (Hariyadi, 2015) This research is in line with one in Surakarta, namely an increase in hemoglobin levels in pregnant women after giving 350 gram long bean leaves for 30 days (Prastika et al, 2016). Other research have shown increased levels of hematocrit in pregnant women after consuming green bean juice (Anastasia S et al, 2017).…”
Section: Resultssupporting
confidence: 76%
“…Damage to blood, even though mainly characterized by hemolysis, can also be subtler. Subhemolytic trauma can result in shortened life spans for red blood cells (RBCs) in patients with prosthetic heart valves as well as VADs [14,15]. The accelerated loss of red cells requires the individual to produce more red cells or contributes to anemia.…”
Section: Introductionmentioning
confidence: 99%
“…This provides a biophysical, biochemical, and immunological system for the development and improvement of extracorporeal and other flow-assist device technologies. 3,26 Also, these findings suggest that, when transfusion becomes necessary during surgery, the youngest available blood bank concentrates are preferred. Neonates, children or adults who depend on extracorporeal oxygenation and/or circulatory support for extended periods may be much more affected by the alterations in RBCs than observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…8 Relatively few studies have addressed the effect of EC on the processes regulating fundamental characteristics of RBCs. 3,9,10 Therefore, we investigated the effect of circulation in a heart-lung machine on physiologically relevant parameters of RBC structure, function, and survival. [11][12][13][14][15][16][17] In order to distinguish the EC-induced changes from those influenced by the patients' circulation, 10,12 we compared the data obtained from a stand-alone extracorporeal circuit with those obtained during EC-assisted cardiac surgery.…”
mentioning
confidence: 99%